2018
DOI: 10.3989/gya.1221172
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of <sup>19</sup>F and <sup>1</sup>H NMR spectroscopy with conventional methods for the detection of extra virgin olive oil adulteration

Abstract: This paper reports the comparison of determination methods for extra virgin olive oil (EVOO) adulteration with two kinds of oils, refined olive oil (ROO) and soybean oil by 19FNMR, 1H NMR and chemical titration. The determination of adulteration of EVOO with ROO by 19F NMR was comparable to the conventional method. The contents of oleic, linoleic and linolenic acids of different oil samples can be determined by both 1H NMR and GC-MS. The results obtained from the two methods showed little differences. The adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 15 publications
1
12
1
Order By: Relevance
“…EVOO is a high quality cold-pressed plant oil because of its nutritional value and health benefits. The D ratio of TOL in our lab is much higher than all EVOO samples detected in our previous papers (Zhou et al, 2015;Jiang et al, 2018b) because all EVOO samples were imported from Spain and Italy to Shanghai at least 1.5 years after being prepared. In addition, the 1,3-DG content of all the other plant oils was higher than 1,2-DGs, and the D ratio D was about 0.3 which is in agreement with the study by Zhou et al (2015).…”
Section: Diglyceride Contentcontrasting
confidence: 49%
See 2 more Smart Citations
“…EVOO is a high quality cold-pressed plant oil because of its nutritional value and health benefits. The D ratio of TOL in our lab is much higher than all EVOO samples detected in our previous papers (Zhou et al, 2015;Jiang et al, 2018b) because all EVOO samples were imported from Spain and Italy to Shanghai at least 1.5 years after being prepared. In addition, the 1,3-DG content of all the other plant oils was higher than 1,2-DGs, and the D ratio D was about 0.3 which is in agreement with the study by Zhou et al (2015).…”
Section: Diglyceride Contentcontrasting
confidence: 49%
“…In addition, there are some minor nutritional components in tea oil that are lost during refining. Some researchers have suggested that the D ratio can be utilized as an index to distinguish different grades of the same kind of oil such as olive oil (Jiang et al, 2018b). Hence, using 19 F NMR to detect adulteration in cold-extracted tea oil with refined tea oil is feasible.…”
Section: Adulteration Of Tea Oil With Refined Tea Oilmentioning
confidence: 99%
See 1 more Smart Citation
“…As a non-destructive detection technique, NMR provides excellent repeatability and reproducibility, and can accurately quantify and provide structural information of the different compounds in a mixture [ 19 , 20 , 21 ]. Recently, NMR techniques, including high-field/low-field NMR (HF-/LF-NMR), have been used to detect CA components [ 22 ], measure the physical and chemical properties of cold-pressed and commercial refined CA [ 23 ], classify vegetable oils, and detect adulteration [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the FT-NIR spectroscopy technique has been extensively used in quality and safety analysis of EVOO [7,8,9]. In addition, other molecular spectroscopy techniques, such as fluorescence spectroscopy [10,11,12], infrared spectroscopy [13,14,15], Raman spectroscopy [16,17,18], and nuclear magnetic resonance spectroscopy [19,20], have good applications in the analysis of EVOO adulteration. With the technological developments, the amount of spectral data acquired is increasingly large because of the improvement of instrument resolution.…”
Section: Introductionmentioning
confidence: 99%